Sustainability assessment and environmental impacts of water supply systems: a case study in Tampa Bay water supply system - Yizhi Shen; Minrui Wei; Bowen Hou (E3S Web of Conferences, 2021)
Due to the accelerated industrial and urbanization development, climate change, and increasing populations and life quality expectations, the issue of drinking water shortage has raised much public awareness. The desalination system has been widely applied to accommodate the growing demand for clean water resources despite the continuous concerns about its relatively higher energy consumption and environmental footprints. This research conducted a case study in the Tampa Bay Regional Surface Water Treatment Plant and Tampa Bay Seawater Desalination Plant in Florida, U.S. It analysed the performance and environmental impacts of conventional and desalination water supply systems on three sides: energy consumption, carbon footprint, and solid waste. Potential negative effects of both water supply systems are generally associated with surface water ecology, groundwater aquifers, coastal environment, and marine organisms. Various environmental impact mitigation plans have been proposed to prevent or restore the detriments caused by carbon dioxide emissions, plant construction, and concentrated brine discharge. Due to the deficiency in freshwater resources, desalination technology is more promising through proper regulations and regional sustainable development.